2014
DOI: 10.1038/ki.2013.449
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide inhibits the renal fibrosis of obstructive nephropathy

Abstract: Hydrogen sulfide has recently been found decreased in chronic kidney disease. Here we determined the effect and underlying mechanisms of hydrogen sulfide on a rat model of unilateral ureteral obstruction. Compared with normal rats, obstructive injury decreased the plasma hydrogen sulfide level. Cystathionine-β-synthase, a hydrogen sulfide-producing enzyme, was dramatically reduced in the ureteral obstructed kidney, but another enzyme cystathionine-γ-lyase was increased. A hydrogen sulfide donor (sodium hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
131
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(141 citation statements)
references
References 46 publications
5
131
1
Order By: Relevance
“…Additionally, H 2 S is not beneficial in all models of renal injury as its effect can vary with the context (70). Whereas H 2 S ameliorates renin-induced hypertension (71), ischemia-reperfusion injury in the kidney and heart (17,20), obstructive kidney injury (72), preeclampsia (73), and hyperhomocysteinemia-induced chronic kidney disease (74) and protects endothelium against high glucose (75), it assumes a pathologic role as a mediator in cisplatinum-induced kidney cell injury (76), streptozotocin-induced pancreatic ␤ cell injury (77), and colon carcinoma (78). These considerations suggest that a critical evaluation of PDE5 inhibitors and H 2 S donors should be done in long term models of kidney injury in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, H 2 S is not beneficial in all models of renal injury as its effect can vary with the context (70). Whereas H 2 S ameliorates renin-induced hypertension (71), ischemia-reperfusion injury in the kidney and heart (17,20), obstructive kidney injury (72), preeclampsia (73), and hyperhomocysteinemia-induced chronic kidney disease (74) and protects endothelium against high glucose (75), it assumes a pathologic role as a mediator in cisplatinum-induced kidney cell injury (76), streptozotocin-induced pancreatic ␤ cell injury (77), and colon carcinoma (78). These considerations suggest that a critical evaluation of PDE5 inhibitors and H 2 S donors should be done in long term models of kidney injury in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have demonstrated that exogenous H 2 S, released via sodium hydrosulfide (NaHS), can ameliorate damage associated with short-term ureteral obstruction 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S has also been found to exhibit antifibrotic effects in obstructed nephropathy and to inhibit the proliferation and differentiation of renal fibroblasts. The antifibrotic mechanisms of H 2 S may involve its anti-inflammation, as well as its blockade of TGF-␤1 and MAPK signaling (5). In this study, we established a streptozotocin-induced diabetic rat model to investigate whether H 2 S has protective effects against diabetic nephropathy.…”
mentioning
confidence: 99%
“…Measurement of H 2 S Content-H 2 S levels were determined by the methylene blue method as described previously (5). The H 2 S concentration in plasma was expressed as micromoles/ liter, whereas the H 2 S content in kidney was expressed in nanomoles/mg of protein.…”
mentioning
confidence: 99%